Factors Associated with Soil-Transmitted Helminths Infections in Children Aged 24-59 Months in Bandung District, Indonesia - Hafidz, Athar Zaidan; Adrizain, Riyadi; Setiabudi, Djatnika (Majalah Kedokteran Bandung, 2025)
Soil-transmitted helminth (STH) infections remain a major public health concern in developing countries, particularly among lower- to middle-income populations with poor sanitation, limited access to healthcare, and inadequate clean water. Preschool-aged children are especially vulnerable due to their developing immune systems and increased nutritional needs. This study aimed to identify factors associated with STH infections among children aged 24–59 months in Bandung District, Indonesia. A case-control design was employed using secondary data from helminthiasis surveillance conducted between October 2019 and January 2023, involving a total of 261 children. The Kato-Katz technique was used to examine stool samples for the detection of STH species. Among them, 30 (11.49%) were infected with soil-transmitted helminths (STH), comprising ascariasis (11.11%), trichuriasis (0.38%), and hookworm infection (0.38%). Bivariate chi-square analysis revealed significant associations with fathers’ education level (p = 0.0003), BPJS-Healthcare participation (p = 0.015), water source (p = 0.015), distance from the water source to the latrine (p = 0.003), and nail hygiene (p = 0.018). Multivariate logistic regression confirmed that distance between water source and pit latrine (OR = 0.265; 95% CI: 0.76–0.92), nail hygiene (OR = 0.318; 95% CI: 0.13–0.76), and participation in BPJS-healthcare program (OR = 0.364; 95% CI: 0.15–0.91) were key determinants of STH infection. These findings highlight the importance of addressing environmental and behavioral factors through public health interventions, including improving access to clean water, promoting personal hygiene, and enhancing parental, particularly paternal education, as essential strategies for reducing the risk of STH in children.